The Effect of Irradiation Distance on Microhardness of Resin Composites Cured with Different Light Curing Units - Cekic-Nagas, Isil; Egilmez, Ferhan; Ergun, Gulfem (European Journal of Dentistry, 2010)
Objectives: The aim of this study was to compare the microhardness of five different resin composites at different irradiation distances (2 mm and 9 mm) by using three light curing units (quartz tungsten halogen, light emitting diodes and plasma arc).Methods: A total of 210 disc-shaped samples (2 mm height and 6 mm diameter) were prepared from different resin composites (Simile, Aelite Aesthetic Enamel, Clearfil AP-X, Grandio caps and Filtek Z250). Photoactivation was performed by using quartz tungsten halogen, light emitting diode and plasma arc curing units at two irradiation distances (2 mm and 9 mm). Then the samples (n=7/ per group) were stored dry in dark at 37°C for 24 h. The Vickers hardness test was performed on the resin composite layer with a microhardness tester (Shimadzu HMV). Data were statistically analyzed using nonparametric Kruskal Wallis and Mann-Whitney U tests.Results: Statistical analysis revealed that the resin composite groups, the type of the light curing units and the irradiation distances have significant effects on the microhardness values (P<.05).Conclusions: Light curing unit and irradiation distance are important factors to be considered for obtaining adequate microhardness of different resin composite groups. (Eur J Dent 2010;4:440-446)
Keywords: Irradiation distance; Light curing units; Microhardness; Resin composites